PENGARUH PRODUK DOMESTIK BRUTO DAN SUKU BUNGA TABUNGAN RUPIAH TERHADAP JUMLAH TABUNGAN RUPIAH PADA BANK-BANK UMUM DI INDONESIA TAHUN 2004-2011 - B01109032, Jumingo (Jurnal Pembangunan dan Pemerataan, 2014)
This study aims to determine the effect of: gross domestic product (X1) to the number of rupiah savings and the effect of interest rate of rupiah savings (X2) to the number of rupiah savings. This study uses secondary data obtained from Bank Indonesia and the Central Bureau of Statistics and other sources that support this research. The data is in the form of time series (data prepared based of time series) from 1st quarter of 2004 up to 4th quarter of 2011, which was analyzed by quantitative descriptive analysis method. The results showed that, GDP has a positive and significant effect on the number of rupiah savings. This is consistent with the research hypothesis and the theory of Keynes who said that the spending of savings depends on income level. While the interest rate of rupiah savings has a negative and significant effect on the number of rupiah savings. This is not consistent with the research hypothesis and Classical theory say that saving is a function of the interest rate, because of the amount of savings increased despite low interest rates. This situation can occur due to: 1). per capita income growing community, 2). People are not too concerned factor in this low interest rate, Keynes said Society believes in a normal interest rate, 3). increasing public confidence in the Bank's products and services offered by commercial banks. Keywords: Gross Domestic Product, Interest Rate, Savings